Author Correction: The contribution of pathogenic variants in breast cancer susceptibility genes to familial breast cancer risk. (December 2017) - Slavin, Thomas; Maxwell, Kara; Lilyquist, Jenna; Vijai, Joseph; Neuhausen, Susan; Hart, Steve; Ravichandran, Vignesh; Thomas, Tinu; Maria, Ann; Villano, Danylo; Schrader, Kasmintan; Moore, Raymond; et al.
A correction to this article has been published and is linked from the HTML version of this article.